Autobiography as a Site of Counter Power: a Study with Special Reference to The Autobiography of a Sex Worker - Jayalakshmi. E. (Singularities : A Transdisciplinary Biannual Research Journal, 2016)
Power always produces a counter power or a powerful resistance. That is a political power capable of challenging the dominant power that is imposed upon the power less. Autobiography is generally considered as a literary space where the icons of the society explain their lives to the people. But today, it has become a weapon for the marginalized to assert both their identity and the identity of their community. It acts as a powerful medium to express dissent or question the power mechanism operating in the society. This paper intends to critically analyse autobiography as a site of counter power by studying the autobiographies of Nalini Jameela Autobiography of a sex Worker) and Sr.Jesme (Amen). These women are doubly marginalized by virtue of their sex and their social status. So their writings are voices from the margin of the margin. This paper attempts to study how these women use autobiography as a powerful tool to exert their power as women to break the Lakshman Rekha of gender and social taboos that powerful sections of the society imposed upon them. For them unlike the icons of the society, writing autobiography is a political act of establishing their identity against the identity that the society imposed on them.